Tanggung Jawab dan Perlindungan Hukum Direksi dalam Pengurusan Perseroan Terbatas - Raffles Raffles (Fakultas Hukum Universitas Jambi, 2020)
This article discusses the responsibilities of directors and their legal protection in managing a limited liability company. The responsibility of the directors in managing a limited liability company as regulated in the 2007 Company Law is related to the duties and authority to run the management of the company for the benefit of the company and in accordance with the aims and objectives of the company. To carry out the management of the company, the directors are authorized to carry out the management of the company in accordance with policies deemed appropriate, within the limits specified in the 2007 Company Law and/or articles of association. The responsibility of members of the directors for the company’s losses can be seen from the nature of the responsibility is personal and collective. The directors’ liability is personal if the loss suffered by the company is due to an error or negligence of the individual members of the board of directors. The responsibility of the directors is collective if the company’s losses are caused by an error or negligence in the board’s decision or action. Legal protection for directors in company management is provided if the management is based on good faith and prudence, which is recognized as the business judgment rule doctrine. Basically, directors are responsible for all actions and decisions they make, even personal accountability. However, directors can avoid personal liability if they can prove the basis and reasons and are based on good faith and caution. Abstrak Artikel ini membahas tanggung jawab dan perlindungan hukum direksi dalam pengurusan perseroan terbatas. Pertanggungjawaban direksi dalam pengurusan perseroan terbatas sebagaimana diatur dalam UUPT Tahun 2007 terkait dengan tugas dan wewenangnya menjalankan pengurusan perseroan untuk kepentingan perseroan dan sesuai dengan maksud dan tujuan perseroan. Untuk menjalankan pengurusan perseroan, direksi berwenang menjalankan pengurusan perseroan sesuai dengan kebijakan yang dipandang tepat, dalam batas yang ditentukan dalam UUPT Tahun 2007 dan/atau anggaran dasar. Pertanggungjawaban anggota direksi atas kerugian perseroan dilihat dari sifat pertanggungjawabannya bersifat pribadi dan kolektif. Pertanggungjawaban direksi bersifat pribadi apabila kerugian yang dialami perseroan disebabkan kesalahan atau kelalaian individu anggota direksi. Pertanggungjawaban direksi bersifat kolektif apabila kerugian perseroan diakibatkan adanya kesalahan atau kelalaian dalam keputusan atau tindakan dewan direksi. Perlindungan hukum terhadap direksi dalam pengurusan perusahaan diberikan jika pengurusan tersebut didasarkan pada itikad baik dan hati-hati, yang dikenali sebagai doktrin business judgement rule. Pada dasarnya direksi bertanggung jawab atas segala tindakan dan keputusan yang dibuatnya, bahkan pertanggungjawaban pribadi. Namun demikian, direksi dapat terhindar dari tuntutan pertanggungjawaban secara pribadi apabila dapat membuktikan dasar dan alasannya dan didasarkan pada itikad aik dan hati-hati.